1988
DOI: 10.1246/bcsj.61.1985
|View full text |Cite
|
Sign up to set email alerts
|

The Cyanation of Aromatic Halides Catalyzed by Nickel(0) Complexes Generated In Situ. I. General Scope and Limitations

Abstract: The cyanation of chlorobenzene catalyzed by Ni(PPh3)n, which was generated in situ from NiBr2(PPh3)2–Zn–PPh3(Ni : Zn : P=1 : 3 : 2 molar ratio), was at first examined with various MCN (M=K, Na)–solvent systems by three procedures in order to clarify the conditions under which the reaction occurs. The effects of the systems and the procedures on the reaction were remarkable. It was observed that the cyanide ion has an inhibitory action on both the reduction of Ni(II) and the oxidative addition of the halide to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…In the case of 3‐nitrobromobenzene (Table 1, entry 5), small amounts of hydrodehalogenation (C 6 H 5 NO 2 ) and nitro‐reduction (BrC 6 H 4 NH 2 ) products were detected but the selectivity of 88 % remains acceptable. Our copper‐based catalytic system is therefore compatible with the nitro substituent, whereas nickel‐catalyzed cyanation of nitro‐substituted aryl halides failed 9a. Note that the presence of an amino substituent also allows the synthesis of the corresponding nitrile in a very good yield and with excellent selectivity (>99 %) (Table 1, entry 4).…”
Section: Resultsmentioning
confidence: 90%
“…In the case of 3‐nitrobromobenzene (Table 1, entry 5), small amounts of hydrodehalogenation (C 6 H 5 NO 2 ) and nitro‐reduction (BrC 6 H 4 NH 2 ) products were detected but the selectivity of 88 % remains acceptable. Our copper‐based catalytic system is therefore compatible with the nitro substituent, whereas nickel‐catalyzed cyanation of nitro‐substituted aryl halides failed 9a. Note that the presence of an amino substituent also allows the synthesis of the corresponding nitrile in a very good yield and with excellent selectivity (>99 %) (Table 1, entry 4).…”
Section: Resultsmentioning
confidence: 90%
“…Sakakibara et al have reported about nickel-based cyanation reactions, unfortunately HMPA was found as the best solvent. [10] More recently, we reported the use of PdA C H T U N G T R E N N U N G (OAc) 2 /n-butyl-di(1-adamantyl)phosphine (Scheme 2, ligand 1) for reactions of aryl chlorides with non-reactive substituents. [11] Most currently, Littke and coworkers described the use of 4 mol% Pd and 8 mol% of a special Buchwald-type ligand (Scheme 2, ligand 2), Zn as additive, and Zn(CN) 2 as cyanide source.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of 3a (Scheme 1) with NaCN/Pd(Ph 3 P) 4 2 /Zn/Ph 3 P in lower boiling solvents (THF or CH 3 CN). 9 In our hands, the best results in the reaction of 2 with NiBr 2 (Ph 3 P) 2 /Zn/Ph 3 P to yield 5a were obtained using CH 3 CN as the solvent (Scheme 2). Reaction of 2 with K 14 CN in the presence of NiBr 2 (Ph 3 P) 2 / Zn/Ph 3 P in refluxing acetonitrile gave 5b in 51% yield.…”
Section: Discussionmentioning
confidence: 87%